Does Inner Awareness Always Accompany Outer Awareness During Perception? - Chaturvedi, Madhu Mangal; Ravishankar Sarma, A. V. (Problemos, 2019)
Ar vidinis žinojimas percepcijos metu visada lydi išorinį žinojimą?